Politics, Law, Regional Innovation Policy Related to the Implementation of Population Administration in Local Government Administration - Tristiana, Enis (Faculty of Law, Universitas Pekalongan, 2024)
Legal politics was originally interpreted as legal policy (legal policy) imposed in certain regions. At the next stage, legal politics is also understood as a frame of mind in determining and understanding the legal policy. Legal politics is the development of law that is based on making and updating material to suit the needs and implementation of legal provisions that have been included in affirming the function of institutions and fostering law enforcers. Regional Innovation is all forms of renewal in the implementation of Regional Government regulated in Government Regulation Number 38 of 2017 concerning Regional Innovation. In population administration, assessments related to regional innovation are regulated in the implementation of population administration. This study was conducted to find out This study uses data collection methods with interviews, observations, and documentation to see the results of research and discussion. Legal politics related to regional innovation policies are all forms of reform in the administration of regional government